Technological profile of systems of milk production of family cattle in the hinterland of Alagoano / Perfil tecnológico de sistemas de produção de leite de bovino familiar no sertão Alagoano - Cleyton de Almeida Araújo; runa Missiele Bras de Oliveira; Deneson Oliveira Lima; Conceição Maria Dias de Lima; Carolina Corrêa de Figueiredo Monteiro; Maria Telma de Aquino Rodrigues (Universidade Estadual de Alagoas, 2019)
Milk cattle farming is one of the livestock activities responsible for generating jobs, income and revitalization of agrarian spaces. The objective was to characterize the technological profile of bovine milk production systems in the Alagoano hinterland. Initially an exploratory research was carried out to select the rural producers in Santana do Ipanema and surrounding municipalities, inserted in the semi-arid region. Thirteen properties were evaluated, with a family profile, and source of primary income from dairy activity. The characterization was performed through an activity / property diagnosis, data were collected between August 2017 and August 2018. The descriptive studies method was used to be quantitatively analyzed inductively. Family units have the full use of family labor. With a high frequency of temporary work (46%). The milking is done manually, and with the presence of the calf in 92% of the properties. However, only 38% have access to an expansion tank. All the properties use native pasture, and 85% have palms. The use of chemical fertilizers obtained a frequency of 23%, and 69% of the population use organic fertilizers, presenting a greater frequency of use when compared to the chemical. The performance of milk, reproductive and economic controls shows a low frequency of use with 38%; 38% and 31% respectively. The production systems presented with low technological level for milk production, a factor that limits the productivity of these cattle ranchers. Several factors may have influenced, among them, access to credit and continued quality technical assistance.